2010
DOI: 10.1007/s10470-010-9512-6
|View full text |Cite
|
Sign up to set email alerts
|

A new robust capacitively coupled second harmonic quadrature LC oscillator

Abstract: A study of some reported superharmonic LC quadrature voltage-controlled oscillator (LC-QVCO) is performed in which it is shown that robustness of the quadrature oscillation varies depending on the coupling configuration. Next, a new superharmonic LC-QVCO is proposed in which the common source node in either of two identical cross-connected LC-VCOs is coupled via a capacitor to the node common between the two varactors in the LC-tank of the other LC-VCO. As a result of connecting common mode nodes, the currents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 14 publications
(33 citation statements)
references
References 16 publications
0
33
0
Order By: Relevance
“…In configuring this circuit the analysis of the superharmonic QVCOs presented in [16] was considered. In [16] it is suggested that the presence of a loop through which the second harmonic signals can circulate leads to the generation of quadrature signals. Based on this idea, the common mode nodes of the two identical core LC-VCOs denoted in Fig.…”
Section: The Proposed Second-harmonic Qvcomentioning
confidence: 99%
See 4 more Smart Citations
“…In configuring this circuit the analysis of the superharmonic QVCOs presented in [16] was considered. In [16] it is suggested that the presence of a loop through which the second harmonic signals can circulate leads to the generation of quadrature signals. Based on this idea, the common mode nodes of the two identical core LC-VCOs denoted in Fig.…”
Section: The Proposed Second-harmonic Qvcomentioning
confidence: 99%
“…receivers and transmitters operating based on the direct modulation and demodulation, respectively [1,2]. Different methods for generating quadrature signals have been introduced so far, some of which are: poly-phase RC-CR filters [2], master-slave flip-flops [2,3], ring-oscillators [4], and coupled LC-oscillators [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. QVCOs based on coupled LC-oscillators are popular in RF circuits because of their relatively low phase noise.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations